Dr. Abdul Sattar Al Jawari between facilitation and renewal - Latif, Inas Abdul Majid (Al-Adab Journal, 2022)
Is Dr. Abdul Sattar Al-Jawari is one of the modern grammar scholars, and although he was influenced by the early sculptors, he prevailed over his statements affecting Professor Ibrahim Mustafa, and was not affected by modern linguistic studies in the West, and that his call-in facilitation will not go beyond the limits of what the ancients put him, as facilitation is shorthand and overcoming the difficult of grammar investigations. The research included a preface in which it dealt with the life of the neighborhood and divided the research into two chapters, the first chapter entitled (facilitation and renewal in grammar) and included two researches, the first of which dealt with the origin and concept of both facilitation and renewal, the causes of facilitation and its sources and the renewal of grammar After that, I moved to indicate the classification of attempts at facilitation, as I explained the methods that go the way, but the second topic of the first chapter came with the title "Grammar facilitation of the ancients and modernists" and it was in two sections, which dealt in paragraph (first) the opinions of the ancients but in the paragraph Secondly, it dealt with the opinions of the modernist, and marked the second chapter (the efforts of the neighborhood between facilitation and renewal) in which it addressed his attempt to facilitate through his four books (towards facilitation, towards the Qur'an, towards action, and towards meanings).